Inventories, markups and real rigidities in sticky price models of the Canadian economy - Oleksiy Kryvtsov; Virgiliu Midrigan (Bank of Canada, 2011)
Recent New Keynesian models of macroeconomy view nominal cost rigidities, rather than nominal price rigidities, as the key feature that accounts for the observed persistence in output and inflation. Kryvtsov and Midrigan (2010a,b) reassess these conclusions by combining a theory based on nominal rigidities and storable goods with direct evidence on inventories for the U.S. This paper applies Kryvtsov and Midrigan's model to the case of Canada. The model predicts that if costs of production are sticky and markups do not vary much in response to, say, expansionary monetary policy, firms react by excessively accumulating inventories in anticipation of future cost increases. In contrast, in the Canadian data inventories are fairly constant over the cycle and in response to changes in monetary policy. Similarly to Kryvtsov and Midrigan, we show that markups must decline sufficiently in times of a monetary expansion in order to reduce firms' incentive to hold inventories and thus bring the model's inventory predictions in line with the data. The model consistent with salient features of the dynamics of inventories in the Canadian data implies that countercyclical markups account for a sizable (50-80%) fraction of the response of real variables to monetary shocks.
Keywords: E31; F12; 330; Business fluctuations and cycles; Transmission of monetary policy; Schock; Betriebliche Preispolitik; Preisrigidität; Lagermanagement; Geldpolitik; Transmissionsmechanismus; Kanada